Model Regulasi Diri dalam Pengembangan Sikap Spiritual MIN 1 Jombang - nimatul - izza (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2020)
Spiritual attitude development as a conscious effort designed to assist individuals in developing knowledge, skills, and personality in spiritual attitudes. Four values ​​in the implementation are applied in primary schools that must be developed, namely, observance of worship, gratitude behavior, praying before and after doing activities, tolerance in worship. Based on this value there is a human relationship with God, humans with humans, and humans with the universe. In a relationship with God, human beings are obliged to perform compulsory worship, even though maintaining their terminology, everyone is not necessarily capable. Good self-regulation by regulating itself affects the process of spiritual attitude done in life. This study aims to describe the development of spiritual attitudes in MIN 1 Jombang. As well as describing the regulation model of MIN 1 Jombang students in carrying out compulsory worship. The research method used in this research is descriptive qualitative which intends to understand the main phenomena in developing spiritual attitudes in MIN 1 Jombang and describing the regulatory models of MIN 1 Jombang students. The findings that can be explained are, the self-regulation model of students in MIN 1 Jombang in maintaining the term of worship to perform compulsory worship tends to be from the external regulation model, the model that is influenced by others to run it, and the existence of these influences which then encourages students to carry out each when and continuously and become a habit, so that without being instructed by others students will do it themselves, the model of self-regulation changes into an intrinsically motivated behavior model in which he feels that worship is a very valuable activity that needs to be done.